Roughage quality determines the production performance of post-weaned Hu sheep via altering ruminal fermentation, morphology, microbiota, and the global methylome landscape of the rumen wall - Ma, Sen; Zhang, Yan; Li, Zidan; Guo, Ming; Liu, Boshuai; Wang, Zhichang; Cui, Yalei; Wang, Chengzhang; Li, Defeng; Shi, Yinghua (Frontiers in Microbiomes, 2024)
Roughage quality is a crucial factor influencing the growth performance and feeding cost of ruminants; however, a systematic investigation of the mechanisms underlying this is still lacking. In this study, we examined the growth performance, meat quality, ruminal fermentation parameters, rumen microbiome, and tissue methylomes of post-weaned Hu sheep fed low- or high-quality forage-based diets. Our results showed that sheep in the alfalfa hay (AG) and peanut vine (PG) groups exhibited better growth performance, slaughter performance, and meat quality than sheep in the wheat straw group (WG). The sheep in the AG possessed relatively higher contents of serum immunoglobins (IgA, IgG, and IgM) and lower contents of serum inflammation factors (TNF-α, IL-1β, IL-6, and IL-8) than those in the WG and the PG did. In addition, the levels of blood T lymphocytes (CD4+ and CD8+) and the CD4-to-CD8 ratio were significantly higher in the AG sheep than in the WG sheep and PG sheep. The concentration of ruminal NH3-N was highest in WG sheep, whereas the concentrations of individual and total short-chain fatty acids (SCFAs) were highest in the PG sheep. The length, width, and surface area of ruminal papillae were markedly different among the three groups, with the sheep in the PG being the most morphologically developed. The main ruminal microbes at the genus level include Prevotella 1, Rikenellaceae RC9 gut group, norank f F082, Ruminococcus 1, and Ruminococcus 2. The relative abundances of certain species are positively or negatively associated with fermentation parameters and growth index. For example, the fibrolytic bacteria Ruminococcaceae UGG-001 showed positive relationships with the concentration of SCFAs, except propionate. In addition, the relative abundances of fibrolytic bacteria (e.g., Ruminoccus 1) showed a negative relationship with starch-degrading bacteria (e.g., Prevotellaceae). The genome-wide DNA methylation analysis revealed that rumen tissues in the PG sheep and WG sheep occupied different global DNA methylomes. The genes with differentially methylated promoters were involved in known pathways (e.g., the FoxO signaling pathway) and the Gene Ontology (GO) terms (e.g., anatomical structure morphogenesis) pertaining to rumen development. Two candidate genes (ACADL and ENSOARG00020014533) with hyper- and hypo-methylated promoters were screened as potential regulators of rumen development. In conclusion, roughage quality determines sheep growth performance via directly influencing rumen fermentation and microbiome composition, and indirectly affecting rumen development at the epigenetic level.